Settlement of Agricultural Land Mortgage Disputes with Agreements Under Hand in North Sumatra Province - Sitinjak, Imman Yusuf; Perdana, Surya; Wajdi, Farid (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to find out why it is necessary to resolve agricultural land mortgage disputes with agreements under hand in North Sumatra Province. The need for dispute resolution is a protection effort for the parties, namely in agricultural land mortgage disputes, when resolving problems and is also a solution to problems if they occur again like today in the future. The research method used is a qualitative research method, with a normative type of research. The research approach is a legislative approach, and a conceptual approach. The sources of research data based on secondary data are laws and regulations, book publications, research, journals and research supporting documents. Literature and documentation data collection tools. The need to resolve agricultural land mortgage disputes with an agreement under hand is due to the legal protection of the interests of the parties which must be prioritized to terminate the legal relationship between the parties in the underhand lien agreement that has been made.